Evaluation of conducts for prevention of hypertensive syndrome specific of pregnancy among teenagers - Marlucilena Pinheiro da Silva; Zélia Maria de Sousa Araújo Santos; Rosana Oliveira do Nascimento; Juliana Lima Fonteles (Rev Rene)
Pregnant teenagers are vulnerable to the occurrence of diseases such as Hypertensive Disorders of Pregnancy (HDP) due to organic immaturity, and misinformation. This is a descriptive study of quantitative approach with the objective of evaluating the conduct in pregnant teenagers in the prevention and/or control of HDP risks, with focus in heath education. It was conducted in a Family Health Basic Unit in Fortaleza — CE, with 25 pregnant women. The data were collected during the months of August and September 2008, through structured interview organized in charts and tables. The pregnant women had precarious socioeconomic conditions, low education level and risk factors of HDP, fragmentation of knowledge and inadequate self-care concerning prevention of this disease were facts that could compromise the satisfactory evolution of pregnancy. The prenatal care must prioritize the educational actions in order to lead those teens to effective practice of self-care in order to promote health and well-being.